Estudo comparativo dos níveis de neurotransmissores no líquor de pacientes com demência com corpúsculos de Lewy, demência da doença de Alzheimer e indivíduos controles - Miraldo, Marjorie Câmara [UNIFESP] (2017)
The early and accurate diagnosis of dementia with Lewy bodies and Alzheimer’s disease dementia needs objective and quantifiable available parameters. These syndromes have many neurodegenerative characteristics in common, which can eventually difficult their differentiation based on the neuropsychological profile. It is known that changes in the metabolism of neurotransmitters are somehow involved in these dementia syndromes. Thus, this study has as main objective the comparative study of neurotransmitter levels in CSF of patients with dementia with Lewy bodies, patients with Alzheimer's disease dementia, and controls without dementia. The levels of the main monoamines were quantified analyzing the content of their metabolites (VMA, MHPG, L-DOPA, DOPAC, 5-HIAA and HVA) as well as neurotransmitter amino acids (Asp, Glu, Gln, Gly, Tau and GABA). The identification of these neurotransmitters as possible cerebrospinal fluid biomarkers, aims at a better diagnostic differentiation among patients with such dementia syndromes. Participants with dementia with Lewy bodies (n = 20) were paired with participants with Alzheimer's disease dementia (n = 20) by gender and cognitive scores (Mini- Mental State Examination and CDR), and paired with controls without dementia (n = 20) by gender and age (± 1 year). Cerebrospinal fluid monoamine metabolites and amino acids were analyzed by high performance liquid chromatography. The concentrations of VMA, 5-HIAA and HVA were lower in both type of patients (dementia with Lewy bodies and in patients with Alzheimer’s disease dementia), when compared with controls without dementia. These data suggest a reduction in the release of norepinephrine, dopamine and serotonin by the brain of patients suffering dementia. Reduced Glu levels in CSF were also found in patients with dementia with Lewy bodies, compared with control subjects, suggesting increased release and metabolization of these neurotransmitters by the brain tissue of these patients. However, despite the alterations found, none of them had difference among the three groups. Thus, this study concluded that none of these neurotransmitters could serve as a specific marker for the dementia syndromes studied.